2007
DOI: 10.1007/s11090-006-9047-x
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Study on the Entrainment of Ambient Air into Subsonic Laminar and Turbulent Argon Plasma Jets

Abstract: Modeling study is performed to reveal the special features of the entrainment of ambient air into subsonic laminar and turbulent argon plasma jets. Two different types of jet flows are considered, i.e., the argon plasma jet is impinging normally upon a flat substrate located in atmospheric air surroundings or is freely issuing into the ambient air. It is found that the existence of the substrate not only changes the plasma temperature, velocity and species concentration distributions in the near-substrate regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…4-7 are roughly consistent with the modeling predictions of Ref. [19][20][21], although the entrained gases are somewhat different (nitrogen is used in this experiment while air is used in the modeling studies). As mentioned above, the plasma-forming gas (argon) of the plasma torch is supplied through three channels, i.e.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…4-7 are roughly consistent with the modeling predictions of Ref. [19][20][21], although the entrained gases are somewhat different (nitrogen is used in this experiment while air is used in the modeling studies). As mentioned above, the plasma-forming gas (argon) of the plasma torch is supplied through three channels, i.e.…”
Section: Resultssupporting
confidence: 78%
“…7, where the variations of the entrained mass flow rate normalized to the jet-inlet mass flow rate (m 1 /m 0 ) are shown as the function of the jet-inlet mass flow rate (m 0 ) for the three different chamber lengths. It is seen that the value of the normalized mass flow rate m 1 /m 0 increases with The modeling study on the entrainment characteristics of turbulent argon thermal plasma jets issuing into ambient air was carried out in [19][20][21]. It was shown that the entrained air mass flow-rate almost linearly increases with increasing jet-inlet gas velocity (or mass flow rate) for a fixed jet-inlet temperature and with increasing axial distance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…the maximum mass flow rate of the ambient air entrained into the turbulent impinging plasma jet was 18 times as large as the argon mass flow rate at the jet inlet. Wang et al [1] also revealed such an important fact that the existence of the substrate significantly enhanced the maximum mass flow rate of the entrained ambient air due to the additional contribution to the air entrainment of the wall jet formed along the substrate surface. For the typical case mentioned above, the substrate causes the enhancement of maximum entrained-air mass flowrate 5.47 times larger for the laminar impinging plasma jet, while 1.56 times larger for the turbulent impinging plasma jet in comparison with corresponding free jets (without accounting for the existence of the substrate) [1].…”
Section: Introductionmentioning
confidence: 97%
“…is conducted in atmospheric air surroundings by use of a turbulent or laminar plasma jet impinging normally upon a substrate (or workpiece), the ambient air will be entrained into the materials processing region, leading to the oxidation of the metallic particles injected into the plasma jet and of the metallic substrate material, while the material oxidation is often not desirable for many cases. According to our previous study [1], for the typical case that the maximum temperature and velocity at the inlet center of an argon plasma jet are 14,000 K and 1,000 m/s, the distance between the plasma jet inlet and the substrate is 80 mm whereas the radius of substrate is 50 mm, a large amount of ambient air would be entrained into the impinging argon plasma jets if no solid or gas shield was employed to prevent the air entrainment: The maximum mass flow rate of the ambient air entrained into the laminar impinging plasma jet was shown to be 2.6 times as large as the argon mass flow rate at the jet inlet, while its turbulent counterpart was even much larger, i.e. the maximum mass flow rate of the ambient air entrained into the turbulent impinging plasma jet was 18 times as large as the argon mass flow rate at the jet inlet.…”
Section: Introductionmentioning
confidence: 99%